2002
DOI: 10.1038/sj.jea.7500196
|View full text |Cite
|
Sign up to set email alerts
|

Results of a multisite study of U.S. residential magnetic fields

Abstract: This paper describes the study design, measurement protocols, and results of a project examining residential magnetic -field exposures at eight sites across the contiguous United States. The goal of the project was to investigate surrogates that have been used in epidemiologic studies to characterize residential magnetic -field exposure. These surrogates include: personal -exposure ( PE ), fixed -location long -term ( LT ), and outside and inside point -in -time ( PIT ) magnetic -field measurements; net -servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 22 publications
3
15
0
Order By: Relevance
“…This observation is consistent with results from a study of potential confounders of wire codes in southern Connecticut, which found that VHCC homes were more likely to be built before 1949 (OR ¼ 73.24; 95% CI 29.53-181.65) (Bracken et al, 1998). It is also consistent with a study in eight sites throughout the US, where VHCC homes tended to be older than UG homes (Rankin et al, 2002).…”
Section: Distribution Of Wire Codes and Magnetic Field Measurementssupporting
confidence: 90%
“…This observation is consistent with results from a study of potential confounders of wire codes in southern Connecticut, which found that VHCC homes were more likely to be built before 1949 (OR ¼ 73.24; 95% CI 29.53-181.65) (Bracken et al, 1998). It is also consistent with a study in eight sites throughout the US, where VHCC homes tended to be older than UG homes (Rankin et al, 2002).…”
Section: Distribution Of Wire Codes and Magnetic Field Measurementssupporting
confidence: 90%
“…However, if investigators are interested in exposures occurring outside the home only, then more 1 d of sampling would be required to adequately capture the intra-individual variability in exposures that are experienced over time regardless of the selected exposure metric. Others (3,5,7,16,25) have also examined the temporal variability of personal magnetic field exposure metrics in adults and have reported similar findings for the exposure metrics assessed in the present study. Thus, there appears to be consensus across several cohorts that exposure measurement error due to temporal variability is much more problematic for those exposure metrics towards the upper tail of the exposure distribution.…”
Section: Power-frequency Magnetic Field Exposure In Mensupporting
confidence: 81%
“…adults at 217 houses across the contiguous USA, Rankin et al (25) reported that average personal magnetic field exposures and long-term fixed site measurements inside the home were strongly correlated (Pearson's: 0.74, Spearman's: 0.78). Based on these results, one may argue that investigators could rely on an area measurement inside the home instead of personal data if there is interest in average exposures among adult men or women.…”
Section: R C Lewis Et Almentioning
confidence: 99%
“…The temporal cycles observed in the 1,000-Home Study parallel those reported in this paper with respect to magnetic fields attributable to transmission lines, distribution lines (whether one, two or three phases, overhead or underground), and grounding currents (whether from distribution lines or within residences), although the latter appear to have a less discernible pattern (Zaffanella 1993). Also, in a measurement study using a subset of residences from a study in eight regions of the U.S. (Rankin et al 2002), Kaune et al (2000) reported that the occurrence of transients displayed the same daily pattern as those observed here and elsewhere for power frequency magnetic fields.…”
Section: Discussionsupporting
confidence: 59%